Analyticity for solution of fractional integro-differential equations. (November 2022) - Blatt, Simon
Abstract: We prove that for a certain class of kernels K ( y ) viscosity solutions of the integro-differential equation ∫ R n ( u ( x + y ) − 2 u ( x ) + u ( x − y ) ) K ( y ) d y = f ( x, u ( x ) ) are locally analytic if f is an analytic function. This extends results in Albanese et al. (2015) in which it was shown that such solutions belong to certain Gevrey classes.